Book review: Pallett, C., Blackeby, K., Bengo, C., Yule, W., Weissman, R., Scott, S. &Fursland, E. (2015). Managing difficult behaviour: How to improve relationships. London: CoramBAAF. 128pp. ISBN: 9781910039366 - Erica Barr (Scottish Journal of Residential Child Care)
Managing difficult behaviour, or as it is sometimes referred 'challenging behaviour' is the subject of many books, articles and training courses within various fields including education, residential child care, foster care, mental health, learning disabilities and elderly care. Working with trauma-experienced and relationally resistant youth can be very challenging. Their early childhood experiences of abuse, neglect and often trauma means that they have very complex needs and difficulty regulating their emotions, which are often expressed through their behaviour (Cairns, 2016). Managing challenging behaviour, or pain-based behaviour (Anglin, 2003) (which I feel is a more helpful and informed term), can be very difficult and is often the cause of multiple placement breakdowns both within residential child care and foster care. Supporting carers to develop the necessary skills to confidently and competently respond to young people in an emotionally attuned way is vital to improving stability of placements and long-term outcomes (Fahlberg, 2012).